2012
DOI: 10.1097/ta.0b013e318265c9fa
|View full text |Cite
|
Sign up to set email alerts
|

Do we glow? Evaluation of trauma team work habits and radiation exposure

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…3 The remaining proportion (15%) of the annual ionizing radiation dose comes from artificial sources, which for some persons consists of medical ionizing radiation. Most human exposure to ionizing radiation comes from natural sources in the environment.…”
mentioning
confidence: 99%
“…3 The remaining proportion (15%) of the annual ionizing radiation dose comes from artificial sources, which for some persons consists of medical ionizing radiation. Most human exposure to ionizing radiation comes from natural sources in the environment.…”
mentioning
confidence: 99%
“…Risks of radiation exposure are well published, and experience level with imaging techniques and level of training play a role. [24][25][26][27] Orthopaedic traumatologists must be especially vigilant because they use fluoroscopy with significant frequency. 28 It may be difficult to compare final intraoperative images with plain radiographs obtained at subsequent postoperative clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of use of fluoroscopy and protective devices in our study were comparable with those in a worldwide study on orthopedic surgeons that reported that more than half of the procedures performed by 61.5% of the surgeons involved radiation exposure, whereas the rates of using lead aprons, thyroid shields, and lead glasses were 65, 30.8, and 2.5%, respectively [ 16 ]. According to a US survey, 50% of the subjects reported that lead aprons were not available and the remaining half reported that they were not appropriately sized [ 20 ]. The other study reported that one out of three orthopedic surgery residents were not provided protective gowns in the U.S. [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Irish orthopedic surgeons also reported that the regular use of dosimeters among the orthopedic trainees was 15% [24], and only 5% of the orthopedic surgeons were reported to wear the TLD during surgery in Turkey [10]. A possible reason for the orthopedic surgeons not preferring to wear the dosimeters is that they may believe that it will affect their performance and make them uncomfortable [20,25]. Another reason may be that if their radiation exposure was greater than the specified limit, they would be prohibited from operating with fluoroscopy for a specified period of time; therefore, they do not routinely wear the personal dosimetry badges [26].…”
Section: Personal Protective Equipment Usementioning
confidence: 99%